The Role of Attachment Styles, Peer Relations, and Affections in Predicting Internet Addiction - Savcı, Mustafa; Aysan, Ferda (Addicta: The Turkish Journal on Addictions, 2016)
The role of attachment styles, peer relations and affections in predicting Internet addiction is scrutinized in this study. It has been conducted with a total of 2,440 volunteer adolescents, out of which 1,588 are females and 852 are males, all between 14 and 19 years old and attending various high schools in Elazığ’s city center. In this study, the short form of the young Internet addiction test, the Relationship Scale Questionnaire, the Friendship Qualities Scale, and the Positive and Negative Affect Scale were used as data collection tools. Collected data were analyzed through correlational, multiple, and stepwise regression analyses. Study findings demonstrate that the independent variables of attachment styles, peer relations, and affections explain approximately 19% of Internet addiction. Furthermore, Internet addiction among adolescents was observed to be predominantly predicted by the variables of negative affection, conflict, and secure attachment. Attachment styles, peer relations, and affections were determined to predict Internet addiction, and the contribution of affections in this prediction is striking. The results are discussed within the framework of the literature, and recommendations have been given for future studies and applications.Citation: Savcı, M., & Aysan, F. (2016). The role of attachment styles, peer relations, and affections in predicting Internet addiction. Addicta: The Turkish Journal on Addictions, 3, 416–432. http://dx.doi.org/10.15805/addicta.2016.3.0028
Keywords: Attachment styles; Peer relations; Affection; Internet addiction; Adolescent